(untitled) (Research, Society and Development, 2022)
The anxiety disorder in teenagers are considered pathological, and this causes the commitment and aggravation in the daily lives of younger people, causing physical and psychological problems. This study aims to analyze the impacts of the disorder of anxiety in the school’s teenagers. It is an integrative review, of a qualitative approach. The search for the data occurred on the Virtual Health Library (VHL), from the following indicators: teenager health; Anxiety disorder; Mental Health, Measuring the Boolean Operator "and". For the selection of the articles, were considered as inclusion criteria, studies in Portuguese, English and Spanish, available in full, in the period from 2015 to 2022. When starting the search, with the crossing of indicators, 1503 were found. After applying the inclusion rest, 62 articles remained, of which answered the guiding question of the study. This research analyzed anxiety disorders in adolescence and the harm brought for rest in heir lives of these young people, leaving sequels for the rest of their lives, especially in mental health. The results led the researcher to reflect on the need for public policies aimed at youth, especially for adolescents in the school phase, which guarantee. In this case were used curricular grid of the public and private education the performance of the professional by psychology that can assess, diagnose, go along and to monitor the adolescents that suffer with disorder of anxiety, with the intention of promoting quality of life and ensure a healthy development for the teenager.